Integration of Takhassus Tahdiz Program into the Islamic Education Curriculum: a Case Study at Mts Tarbiyatut Tholabah - Khoridatul Azizah; Saiful Islam Al-Ghozi (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
The integration of the Takhassus Tahfidz program into the Islamic education curriculum represents a systemic effort to unify Qur’anic memorization with the structure of formal education, aiming to strengthen students’ spiritual dimension and religious character. At MTs Tarbiyatut Tholabah Lamongan, this program is comprehensively implemented as part of the core curriculum rather than merely an extracurricular activity. This study aims to identify the tahfidz learning strategies employed and to analyze the supporting factors contributing to students’ memorization achievements within a pesantren-based school context. Employing a qualitative descriptive approach, data were collected through interviews and classroom observations of the program’s implementation in Grade VIII F, focusing on planning, execution, and evaluation of instruction. The findings indicate that the program’s success is supported by an integrative curriculum design, contextual pedagogical strategies, the involvement of tahfidz instructors as spiritual mentors, and strong managerial support from the institution. Grade VIII F exceeded its memorization targets, demonstrating that the adopted approach effectively fosters student discipline, spirituality, and academic achievement